A domain and noise adversarial bird tune classification pipeline using deep neural network - Riya, Aparna Sarker; Roy, Arpita; Fahim, Md. Abrar; Tasnim, Zarin; Islam, Rakibul (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.